The Role of Educators in Implementing Disciplined Character in Children - Efendi, Efendi; Misdawati, Misdawati; Eka Putri, Yuliana; Putri, Rika (Journal of Islamic Early Childhood Education, 2024)
Education and application of discipline character in children should be started as early as possible. Through discipline character, children are taught to behave according to established standards. In this study, the role of teachers in applying discipline character in Sholeh toddler playgroup is examined. There are specific problems in the role of educators in applying discipline character in children. This study aims to determine the extent of the role of educators in applying discipline character in Sholeh toddler playgroup in Agam Regency. This type of research uses qualitative research methods with a qualitative descriptive approach. The data in this study were taken directly to the field, namely the research location at KB Balita Sholeh in Salareh Aia Barat village, Palembayan sub-district, Agam Regency. The data sources used in this study are primary and secondary data. Data collection techniques used are observation, interviews, and documentation. The technique of guaranteeing data validity uses source triangulation. Meanwhile, the data analysis technique in this study uses data reduction, data presentation, and drawing conclusions or verification. The results of this study are concluded that the role of educators in applying discipline character in Sholeh toddler playgroup has shown development with good results. This is proven by the actions or attitudes shown by the children, including the children have started to maintain the neatness and cleanliness of the classroom, line up neatly and orderly and many of them have obeyed the rules at school